Autoantibodies as predictors for clinical outcome and toxicity for immunotherapy - Hassel, Jessica C.; Luke, Jason (Clinical cancer research, 2022)
Peripheral blood autoantibody signatures might be useful biomarkers of immunotherapy outcome. Signatures predicting melanoma recurrence and toxicity during adjuvant immunotherapy were recently presented. Whether autoantibodies are bystanders or have a pathophysiologic role is unknown, and further efforts are needed to investigate potential mechanisms and determine causation.See related article by Johannet et al., p. 4121
Gesehen am 25.10.2022